Structural analysis and unique molecular recognition properties of a Bauhinia forficata lectin that inhibits cancer cell growth. (1st February 2017) - Lubkowski, Jacek; Durbin, Sarah V.; Silva, Mariana C. C.; Farnsworth, David; Gildersleeve, Jeffrey C.; Oliva, Maria Luiza V.; Wlodawer, Alexander
Abstract : Lectins have been used at length for basic research and clinical applications. New insights into the molecular recognition properties enhance our basic understanding of carbohydrate–protein interactions and aid in the design/development of new lectins. In this study, we used a combination of cell‐based assays, glycan microarrays, and X‐ray crystallography to evaluate the structure and function of the recombinant Bauhinia forficata lectin (BfL). The lectin was shown to be cytostatic for several cancer cell lines included in the NCI‐60 panel; in particular, it inhibited growth of melanoma cancer cells (LOX IMVI) by over 95%. BfL is dimeric in solution and highly specific for binding of oligosaccharides and glycopeptides with terminal N ‐acetylgalactosamine (GalNAc). BfL was found to have especially strong binding (apparent K d = 0.5–1.0 nm ) to the tumor‐associated Tn antigen. High‐resolution crystal structures were determined for the ligand‐free lectin, as well as for its complexes with three Tn glycopeptides, globotetraose, and the blood group A antigen. Extensive analysis of the eight crystal structures and comparison to structures of related lectins revealed several unique features of GalNAc recognition. Of special note, the carboxylate group of Glu126, lining the glycan‐binding pocket, forms H‐bonds with both the N ‐acetyl of GalNAc and the peptide amido group of Tn antigens. Stabilization provided by Glu126 is described here for the first time for any GalNAc‐specific lectin. Taken together, the results provide new insights into the molecular recognition of carbohydrates and provide a structural understanding that will enable rational engineering of BfL for a variety of applications. Database: Structural data are available in the PDB under the accession numbers 5T50, 5T52, 5T55, 5T54, 5T5L, 5T5J, 5T5P, and 5T5O . Abstract : A combination of cell‐based assays, glycan microarrays, and X‐ray crystallography was used to evaluate the structure and function of the recombinant Bauhinia forficata lectin. The lectin was found to have especially strong binding to the tumor‐associated Tn antigen and was shown to be cytostatic for several cancer cell lines included in the National Cancer Institute‐60 panel.